Caregiver perceptions of a fruit and vegetable prescription programme for low-income paediatric patients - Saxe-Custack, Amy; Lofton, Heather Claire; Hanna-Attisha, Mona; Victor, Colleen; Reyes, Gwendolyn; Ceja, Tiffany; LaChance, Jenny (Public health nutrition, 2018)
The physical and social environments that surround children should support good health. However, challenges with food security and access prevent many children from consuming a healthy diet, which is critical to proper growth and development. The present study sought to gain a better understanding of primary care initiatives to address these issues in a low-income setting. Following the relocation of a paediatric clinic to a farmers' market building and the implementation of a fruit and vegetable prescription programme, researchers conducted thirty-two semi-structured interviews with caregivers. Researchers elicited caregivers' perceptions of clinic co-location with the farmers' market; experiences with the prescription programme; opinions of the farmers' market; and perceived impact on child consumption of fresh produce. Interview recordings were transcribed for textual analysis. Using thematic analysis, researchers examined qualitative data to identify patterns across transcripts and formulate emerging themes. Researchers concluded when data saturation was reached. Flint, Michigan, USA. The majority of participants were female (91 %) and African American (53 %). Four recurrent themes emerged during interviews: (i) convenience of relocation; (ii) attitude towards prescription programme; (iii) challenges with implementation; and (iv) perceived impact of combined interventions. Caregivers indicated that the co-location and prescription programme increased family shopping at the farmers' market, improved access to high-quality produce and improved food security. A fruit and vegetable prescription programme involving a partnership between a farmers' market and paediatric clinic was perceived as effective in improving food security, food access and child consumption of fresh fruits and vegetables.